2017
DOI: 10.1038/labinvest.2016.141
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic role of endogenous TNF-α in the development of Sjögren's-like sialadenitis and secretory dysfunction in non-obese diabetic mice

Abstract: Patients with Sjögren’s syndrome (SS), an autoimmune disease primarily affecting the exocrine glands, exhibit enhanced TNF-α expression in the saliva and salivary glands. However, the precise in vivo role of TNF-α during the initiation and development of SS is not clearly defined. The present study is undertaken to determine the function of endogenously produced TNF-α in the pathogenesis of SS in non-obese diabetic (NOD) mice, a model of this human disease. Administration of a neutralizing anti-TNF-α antibody … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 46 publications
2
48
0
Order By: Relevance
“…One intriguing finding in this study is that administration of anti-CXCR3 antibody exacerbates the production of ANA and anti-M3R autoantibodies. We and other groups have reported the negative correlation between the autoantibody production and TNF-α pathway [16,48,49]. We thereby speculate that the appearance of excessive autoantibodies caused by CXCR3 blockade is the consequence of diminished TNF-α production.…”
Section: Discussionsupporting
confidence: 50%
See 4 more Smart Citations
“…One intriguing finding in this study is that administration of anti-CXCR3 antibody exacerbates the production of ANA and anti-M3R autoantibodies. We and other groups have reported the negative correlation between the autoantibody production and TNF-α pathway [16,48,49]. We thereby speculate that the appearance of excessive autoantibodies caused by CXCR3 blockade is the consequence of diminished TNF-α production.…”
Section: Discussionsupporting
confidence: 50%
“…Expression of CXCL9, CXCL10, and CXCL11 can be up-regulated by pro-inflammatory cytokines, including IFN-γ and TNF-α, in a variety of cell types [13][14][15]. Consistent with this, our recent study demonstrated the down-regulation of CXCL9 in the salivary glands of an SS-like mouse model as a result of TNF-α blockade [16]. CXCR3 ligands play important roles in the pathogenesis of various inflammatory and autoimmune diseases [13,[17][18][19][20][21].…”
Section: Introductionsupporting
confidence: 64%
See 3 more Smart Citations